Proceedings of the 2008 InSITE Conference 2008
DOI: 10.28945/3229
|View full text |Cite
|
Sign up to set email alerts
|

Using Roles of Variables to Enhance Novice's Debugging Work

Abstract: Debugging skill is an essential part of the programming skills. It is also highly related with program comprehension skills. In this paper we present a novel tool, called ViLLE, which supports learning debugging by promoting students' understanding of target program. ViLLE combines visual debugging features with the support for roles of variables. These roles promote activating schemas of variable use in programs. In addition, ViLLE supports automatic presentation of the target program in different programming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…From the literature, a few tools have been developed for teaching/learning programming languages. Some of them adopt role of variable concept such as PlanAni [22] and ViLLE [23,24], others are not, such as OOP-ANIM [8] and Jeliot [25,26,27]. PlanAni and ViLLE tools are used for procedural programming understanding while OOP-ANIM and Jeliot are used for object oriented programming comprehension.…”
Section: Related Workmentioning
confidence: 99%
“…From the literature, a few tools have been developed for teaching/learning programming languages. Some of them adopt role of variable concept such as PlanAni [22] and ViLLE [23,24], others are not, such as OOP-ANIM [8] and Jeliot [25,26,27]. PlanAni and ViLLE tools are used for procedural programming understanding while OOP-ANIM and Jeliot are used for object oriented programming comprehension.…”
Section: Related Workmentioning
confidence: 99%
“…According to our currently search and based on what we found, a few tools have been developed for teaching/learning programming languages. Some of them adopt role of variable concept such as PlanAni [9] and ViLLE [10,11], others are not, such as OOP-ANIM [12] and Jeliot [13,14,15]. PlanAni and ViLLE tools are used for procedural programming understanding while OOP-ANIM and Jeliot are used for object oriented programming comprehension.…”
Section: Related Workmentioning
confidence: 99%
“…Roles represent programming knowledge on a level higher than the simple programming language knowledge, which are always utilized by experts and experienced programmers (Sajaniemi & Prieto, 2005) and can be explicitly taught to the novices (Kohn, 2017). Studies have shown that roles of variables could improve novice code comprehension and debugging skills (Byckling & Sajaniemi, 2006;Sajaniemi & Kuittinen, 2005) and help students in building more general and abstract understanding of the program structures (Al- Barakati & Al-Aama, 2009; and the relation to problem domain concepts (Laakso et al, 2008). Teaching the concepts of roles of variables in the novice programmers learning can help them to understand the different methods of using variables in a program (Taherkhani & Malmi, 2013).…”
Section: Roles Of Variablesmentioning
confidence: 99%